Direito processual penal do inimigo e devido processo legal - Correra, Marcelo Carita (2024)
This thesis concerns about the tension between individual freedom and state power. There was, after the French Revolution, a concern about the limits of state power. The citizens were raised to the status of holders of power. In Brazil, the 1988 Constitution of the Federative Republic, called the Citizen- Constitution, in its first article, declares that the dignity of the human person is the foundation of the State. It is a principle that radiates and binds all legal provisions. In the same sense are the foundations of the American Convention on Human Rights (ACHR). The specific object of study is the application of Criminal Procedural Law as a relevant instrument in the preservation of fundamental rights and enforcement. The theme is relevant, especially in the so-called emergency measures. The method used was the logical-deductive, based on the bibliographic review of national and foreign authors. The precedents of higher courts, especially in common-law countries, were also studied. It is qualitative research but supported by quantitative research to develop specific points. There was a relevant delimitation of the field of study. The Criminal Law of the Enemy (especially in the procedural bias) is the focus. We sought to analyze the institute and its application against crimes that affect the national security (terrorism, for example). The preventive bias and guarantee of the legal order conveyed by the Criminal Law of the Enemy was confronted with the unavoidable need to guarantee fundamental rights. The research demands to determine whether the reduction of fundamental rights, especially in the criminal procedural is compatible with a guaranteeing criminal procedural law and, if so, to what extent. If the preventive character and the need to combat serious crimes authorize the application of the Criminal Law of the Enemy in legal regimes such as Brazil. It was possible to conclude that, despite differing opinions, the institute does not promote the objectification of the human being, but a reduction of rights to reconcile the demands of contemporary society with the principles and guarantees. It is possible, especially considering the harmonization of constitutional principles, to adapt the institute to the country's legal systems in time of peace, to increase the effectiveness of criminal and criminal procedural rules but preserving the minimum guarantees